2004
DOI: 10.1177/10634266040120040101
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance Effects of an Evidence-Based Prevention Innovation for Aggressive Children Living in Culturally Diverse Urban Neighborhoods

Abstract: The present study assessed the ability of the Early Risers' Skills for Success Program to maintain program effects 1 year post intervention. Participants were 327 kindergarten and first-grade children who screened positive for aggressive behavior and who were randomized to program and control conditions. Program children participated in 2 continuous years of active intervention followed by 1 year of no formal intervention activities. Following the active intervention phase, program children, compared to contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
71
0
2

Year Published

2007
2007
2013
2013

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 53 publications
(81 citation statements)
references
References 15 publications
8
71
0
2
Order By: Relevance
“…In contrast to these findings, a number of studies demonstrated that lower parent participation is linked to higher severity of child behavior problems (Orrell-Valente, Pinderhughes, Valente, Laird & Conduct Problems Prevention Research Group, 1999;Bauman et al, 2001;August et al 2003;Dumas et al, 2006;Quinn et al, 2010). For example, some research indicates a negative association between family participation and child aggression (Quinn et al, 2010).…”
Section: Youth Behavioral Characteristics and Parental Engagementmentioning
confidence: 80%
See 3 more Smart Citations
“…In contrast to these findings, a number of studies demonstrated that lower parent participation is linked to higher severity of child behavior problems (Orrell-Valente, Pinderhughes, Valente, Laird & Conduct Problems Prevention Research Group, 1999;Bauman et al, 2001;August et al 2003;Dumas et al, 2006;Quinn et al, 2010). For example, some research indicates a negative association between family participation and child aggression (Quinn et al, 2010).…”
Section: Youth Behavioral Characteristics and Parental Engagementmentioning
confidence: 80%
“…In contrast, Byrnes and colleagues (2011) concluded that higher levels of neighbor-2.1.1 Variables demográficas y contextuales Los trabajos empíricos previos han identificado una serie de variables demográficas y contextuales que parecen estar vinculadas a la baja participación familiar. Algunos de los resultados acumulados sobre este tema indican que las familias con padres de baja asistencia presentan las siguientes caracterís-ticas específicas: a) bajo nivel de estudios y bajo nivel socioeconómico; b) familias monoparentales; c) ausencia del padre biológico en el hogar; y d) familia numerosa (Bauman, Ennett, Foshee, Pemberton y Hicks, 2001;Haggerty et al, 2002;August et al, 2003;Heinrichs, Bertram, Kuschel, y Hahlweg, 2005;Coatsworth, Duncan, Pantin y Szapocznik, 2006;Connell et al, 2007). Por otra parte, Barkley y colegas (2000) observaron que el nivel de estudios de los padres era un predictor más potente de participación parental que el nivel socioeconómico o la depresión parental.…”
Section: Demographic and Contextual Variablesunclassified
See 2 more Smart Citations
“…First, whereas the prototype conforms to an indicated prevention approach and qualifies children on the basis of sub-clinical levels of aggressive and disruptive behavior, the community integration model uses a selective approach making it compatible with the service mandate of community sector-of-care agencies (see August et al, 2003). As such, children are eligible for program services based on their family's residence in supportive housing regardless of their status on mental health risk indicators.…”
Section: Early Risers Prevention Service: Community Integration Modelmentioning
confidence: 99%